2017
DOI: 10.1186/s12913-017-1991-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and utilization of generic medicines in Guatemala: a mixed-methods study with physicians and pharmacy staff

Abstract: BackgroundAccess to low-cost essential generic medicines is a critical health policy goal in low-and-middle income countries (LMICs). Guatemala is an LMIC where there is both limited availability and affordability of these medications. However, attitudes of physicians and pharmacy staff regarding low-cost generics, especially generics for non-communicable diseases (NCDs), have not been fully explored in Guatemala.MethodsSemi-structured interviews with 30 pharmacy staff and 12 physicians in several highland tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
1
20
0
3
Order By: Relevance
“…Again generic prescription leads to clarity of information among the health professionals [36]. The poor generic prescribing may be attributed to physicians' doubt towards prescribing low-cost generic medicines for hypertensive and diabetic patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…Again generic prescription leads to clarity of information among the health professionals [36]. The poor generic prescribing may be attributed to physicians' doubt towards prescribing low-cost generic medicines for hypertensive and diabetic patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…Most experience about the knowledge and perceptions regarding generics comes from interviews and surveys conducted in cross sections of populations in various countries [12,27,42,43]. There is lack of a standard approach for the assessment of knowledge, attitudes, and perceptions about generics.…”
Section: Recommendationsmentioning
confidence: 99%
“…Based on the study conducted by Flood et al (2017) about the perception and utilization of generic drugs in Guatemala, the research targets were doctors and pharmacists. There were 12 doctors and 30 pharmacy staff from three locations in Central Guatemala.…”
Section: Doctors' Obediencementioning
confidence: 99%
“…The doctors who became the respondents admitted that the quality of generic drugs depended on the capability of companies which produced the generic drugs, and the low price of generic drugs showed their inadequate quality. From the research conducted by Flood et al (2017), it could be concluded that doctors' perception of generic drugs influenced their willingness to use generic drugs for patients, therefore it also influenced their adherence in medicines prescription by using generic drugs. Whereas basically, generic drugs are one of the pharmaceutical preparations that have fulfilled the pharmacopeia requirements and passed the manufacturing process according to the article about how to produce proper medicinal drugs (Yusuf, 2016).…”
Section: Doctors' Obediencementioning
confidence: 99%